The Occupational Wellness Concerns and Self-Care Strategies of Filipino Medical Social Workers During The COVID-19 Pandemic - Imperial, Patricia Marie; Abes, Veronique Ann Claire; Ronquillo, Michael John; Vilegas, Mari Allana Corazon (Asean Social Work Journal, 2023)
Given the intense demands imposed on medical social workers (MSWs) during the COVID-19 pandemic, they are vulnerable to developing occupational wellness concerns (OWCs): physical, social, emotional, mental, or spiritual issues caused by work-related factors. OWCs adversely affect the occupational wellness of the worker and the quality of service given to clients. One approach to reduce OWCs is professional self-care. This study explored the experiences of Filipino MSWs during the pandemic, the OWCs experienced, their self-care strategies, and their impact on professional practice. Face-to-face, Zoom, and email interviews were conducted with 10 MSWs who were part of the skeletal workforce of four (4) hospitals in Metro Manila. The findings showed that OWCs were caused by their commitment to professional duty, intense workload, and health and safety risks. This resulted in conflict with coworkers, desire to quit work, undesirable work attitudes, unhealthy habits, and disruption in the quality of service provision. Meanwhile, professional self-care led to enhanced work performance, improved relations with coworkers and clients, enhanced cognitive ability, increased self-awareness, and acted as a first aid response to combat OWCs. Insights on hospital limitations, supportive mechanisms, social work as an undervalued versus satisfying profession, motivation, and professionalism during the pandemic were also documented.